Trends of Empiric Antibiotic Usage in a Secondary Care Hospital, Karachi, Pakistan - Syed Rehan Ali; Shakeel Ahmed; Heeramani Lohana (Hindawi Limited, 2013)
Objectives. (1) To determine the indications, frequency, and types of antibiotics used in hospitalized paediatric patients at tertiary care hospital and (2) to evaluate whether the prescribed antibiotics were based on the isolation of organism and their sensitivity. Study Design. Descriptive observational hospital based study. Results. A total of 131 patients were included over 6 months of study period, in whom antibiotics were prescribed at the time of admission. The majority were between 1 and 5 years of age. M : F ratio was 1 : 1. Fever was the commonest symptom (in 84% of cases) followed by gastroenteritis. Blood culture was done in 114 cases (87%) and was positive only in 10 (8.8%). The commonest organism isolated from blood was Salmonella Typhi. Ceftriaxone was found to be the most frequently prescribed antibiotic as an empirical therapy. 102 (77.86%) patients received Ceftriaxone, followed by ampicillin. The antibiotics were probably used on the basis of clinical condition rather than the result of blood culture, as yield of blood culture was quite low. Conclusion. Our study showed an unjustified use of antibiotics regardless of the admission and discharge diagnosis in acute febrile illnesses. Further on, inappropriate practice of using Ceftriaxone was noted in LRTI and pneumonia. Efforts are needed to educate physicians about the rational use of antibiotics.